320 Liver Transcriptome Analysis Reveals Important Genes Involved in the Feed Efficiency of Lactating Cows Fed a High and Low Starch Diet. (8th October 2021) - Dai, Xiaoxia; Li, Wenli; Fischer, Amelie; Kalscheur, Kenneth
Abstract: The objectives of this study were to identify different gene expression and metabolic pathways in the liver associated with feed efficiency of lactating cows fed high or low starch diets. Ten lactating cows were involved in a cross-over design experiment consisting of two 56-d treatment periods with 11-d diet adaptation fed either high starch (HS; 27% starch) or low starch (LS; 13% starch) diets. Feed efficiency, measured by residual feed intake (RFI), was estimated based on the difference between observed and expected metabolizable energy intake within each experimental period. The 3 highest RFI cows were considered high RFI (HRFI), the 3 lowest RFI cows were considered low (LRFI), and the remaining 4 cows were considered medium (MRFI) in each experimental period. Total RNA was used for next-generation RNA sequencing analysis. Raw reads were mapped to the cattle genome (UMD3.1) using STAR. Differential gene expression analysis was done using Cufflinks. We discovered 642 differentially expressed genes (DEGs) between HS and LS (FDR< 0.05) with 240 genes upregulated and 402 genes downregulated for HS versus LS diet. Via gene-set enrichment analysis (GSEA) analysis (FDR< 0.05), these genes were enriched in 25 gene ontology (GO) pathways related to mitochondria components and 4 GO biological processes involved in peptide metabolism. There were 1427 DEGs impacted by RFI (FDR< 0.05), of which 829 were upregulated, and 598 were downregulated in LRFI compared to HRFI. The 6 GO biological processes enriched by these genes were mainly related to organic substrate metabolism processing and carbon metabolism (FDR< 0.05). Between the DEGs affected by diet and RFI, 522 DGEs were unique to diet and 1307 DEGs were unique to RFI. Our results suggested that genes contributing to different RFIs and the ones associated with the dietary starch treatment may impact distinct pathways. Further functional annotation of these genes may improve feed efficiency.